Civil Resistance from the End of the Cold War to the 21st Century: A Historical Perspective (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2022)
Civil resistance made a significant contribution to the largely peaceful end of the Cold War and has become an increasingly important factor of post-Cold War international politics. This essay proposes a historical reflection of civil resistance from the end of the Cold War to the present, in relation to some crucial issues on the contemporary international scenario. Taking 1989 as the starting point, the main aim of this study is to explore the legacy of the “Long 1989” in the evolution of civil resistance. The essay focuses on three main issues: i) the rise and decline of the post-1989 liberal cycle of civil resistance in Europe; ii) the consequences of the Tiananmen Square Massacre and the emergence of a new Chinese authoritarian state capitalism; and iii) the impact of the technological and digital revolution on post-1989 civil resistance.
Keywords: Civil Resistance; Transnational History; Social Movements; Global History; the Long 1989